(untitled) (Sir Salimullah Medical College Journal, 2022)
Background : Avascular necrosis (AVN), also known as osteonecrosis of femoral head is a pathology in which many etiologies play role and cause decreased vascular supply to subchondral bone of femoral head which results in osteocyte death. MRI is the most sensitive modality for detection of AVN and is helpful for screening and detecting at early stage. Purpose: The aim of the study was to determine the prevalence pattern and stages of presentation of Avascular Necrosis (AVN) of the femoral head. Materials and Methods: This was a retrospective study carried out at the department of Radiology & Imaging, National Institute of Traumatology & Orthopedic Rehabilitation (NITOR), Dhaka where MRI of the hip joint was performed during our study period, only those patients which showed positive signs for avascular necrosis of femoral head were included and were analysed over a period of five years. The age, sex, laterally distribution, causative factors, staging according to Ficat and Arlet classification was done. Results: It was found that most commonly males of productive age group (21 to 40 years) were affected. Though most of them had unilateral involvement however number of bilateral cases were also significant. Mostly, patient presented with stage-IV disease accounting for 104 out of 152 patients (68.42%). Conclusion: Considering that the young males were commonly affected and presented with advanced stage disease at the time of diagnosis, it was recommended that screening MRI should be done in all patients presenting with hip complaints. Sir Salimullah Med Coll J 2022; 30: 180-185